The Process of Authentication - Gorayeb, Elizabeth; Martin, James; Kanter, Laurence; Cohen, Sherri North (The Columbia Journal of Law & the Arts, 2012)
Pippa Loengard: Good morning, everyone. We’re going to get right back into things with our first panel discussion of the day. Sherri North Cohen is going to be our moderator, and we have Larry Kanter, Liz Gorayeb and Jamie Martin, so it’s going to be a wonderful morning. Sherri is the Director of Underwriting at the ARIS Title Insurance Company. She has experience with Holocaust claims and title issues. She’s going to describe her position more, in addition to a little bit about what ARIS does, and its title insurance role in the process that we’re discussing today. We’ll then start the panel. Sherri? Sherri North Cohen: Thanks, Pippa. I head up the underwriting team at ARIS Title Insurance Corporation. We are a New York-based and regulated title insurer that focuses solely on covering the ownership or title risk for the global fine art and collectables market. I’m delighted to be here today to talk about and moderate a panel on the authentication process. This promises to be an insightful discussion about the nuts and bolts of how experts with different qualifications, backgrounds and skill sets authenticate fine art.